PRESEPSI GURU TERHADAP KONSEP SERVICE LEARNING DALAM PEMBELAJARAN IPAS SEKOLAH DASAR - Irma Inesia Sri Utami; Nafisah Deviyanti (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aimed to explore elementary school teachers’ perceptions of the concept of service learning in the context of IPAS (Integrated Science and Social Studies) learning. The research was conducted in May 2025 at a public elementary school in Bogor, West Java, using a descriptive qualitative design. Data were collected through an open-ended online questionnaire and in-depth interviews with six teachers of grades V and VI. The data were analyzed through thematic analysis consisting of data reduction, categorization, and conclusion drawing, supported by triangulation of techniques. The findings revealed that teachers had carried out classroom practices related to real-life issues, such as waste management, bringing healthy lunch, and environmental awareness, which reflected elements of service learning. However, these activities were still limited to the school context, without structured reflection or broader community involvement. Teachers’ understanding of the concept was still developing, yet their perception of its benefits in fostering students’ empathy, social skills, and responsibility was consistently positive. Moreover, all teachers expressed readiness to implement service learning in IPAS, although institutional support and systematic guidelines remain limited.